Attentional reorienting triggers spatial asymmetries in a search task with cross-modal spatial cueing. - Rebecca E Paladini; Lorenzo Diana; Giuseppe A Zito; Thomas Nyffeler; Patric Wyss; Urs P Mosimann; René M Müri; Tobias Nef; Dario Cazzoli (PLoS ONE, 2018)
Cross-modal spatial cueing can affect performance in a visual search task. For example, search performance improves if a visual target and an auditory cue originate from the same spatial location, and it deteriorates if they originate from different locations. Moreover, it has recently been postulated that multisensory settings, i.e., experimental settings, in which critical stimuli are concurrently presented in different sensory modalities (e.g., visual and auditory), may trigger asymmetries in visuospatial attention. Thereby, a facilitation has been observed for visual stimuli presented in the right compared to the left visual space. However, it remains unclear whether auditory cueing of attention differentially affects search performance in the left and the right hemifields in audio-visual search tasks. The present study investigated whether spatial asymmetries would occur in a search task with cross-modal spatial cueing. Participants completed a visual search task that contained no auditory cues (i.e., unimodal visual condition), spatially congruent, spatially incongruent, and spatially non-informative auditory cues. To further assess participants' accuracy in localising the auditory cues, a unimodal auditory spatial localisation task was also administered. The results demonstrated no left/right asymmetries in the unimodal visual search condition. Both an additional incongruent, as well as a spatially non-informative, auditory cue resulted in lateral asymmetries. Thereby, search times were increased for targets presented in the left compared to the right hemifield. No such spatial asymmetry was observed in the congruent condition. However, participants' performance in the congruent condition was modulated by their tone localisation accuracy. The findings of the present study demonstrate that spatial asymmetries in multisensory processing depend on the validity of the cross-modal cues, and occur under specific attentional conditions, i.e., when visual attention has to be reoriented towards the left hemifield.